1981
DOI: 10.1152/ajpheart.1981.240.4.h576
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac contractility and sarcolemmal calcium binding in several cardiac muscle preparations

Abstract: Striking correlations are found between cardiac contractility and Ca2+ binding to isolated cardiac sarcolemma in rabbit, neonatal rat, and frog ventricular tissue. Deviations from this correlation are seen in the adult rat ventricle and rabbit atrium. The observation of this correlation in the three former tissues and under various ionic conditions suggests that this correlation is not coincidental and that Ca2+ bound to the cardiac sarcolemma is of major importance in the control of myocardial contractility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 0 publications
5
27
0
Order By: Relevance
“…The influence of PXB on Ca fluxes is of interest. The observed slowing of Ca uptake (^0.1 mM PXB) is consistent with observations correlating the quantity of Ca bound to the membrane with cell contractility and the magnitude of Ca influx (Bers and Langer, 1979;Bers et al, 1981). Control of Ca binding and flux resides in both the glycocalyx and the lipid bilayer, whereas control of K permeability resides only at the bilayer .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The influence of PXB on Ca fluxes is of interest. The observed slowing of Ca uptake (^0.1 mM PXB) is consistent with observations correlating the quantity of Ca bound to the membrane with cell contractility and the magnitude of Ca influx (Bers and Langer, 1979;Bers et al, 1981). Control of Ca binding and flux resides in both the glycocalyx and the lipid bilayer, whereas control of K permeability resides only at the bilayer .…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, convincing evidence was provided that, rather than binding to the protein or saccharide moieties of the membrane, PXB (at 0.1 mM) interacts preferentially with the lipid moiety, specifically the anionic phospholipids. Since the anionic phospholipids are the major site of Ca binding in cardiac tissue (Philipson et al, 1980), and since Ca binding is directly related to the contractility of this tissue (Bers and Langer, 1979;Bers et al, 1981), PXB may be a useful probe for study of the role of this component in the control of transsarcolemmal Ca and K movements and Ca binding. The results of the present study support this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the T tubule is the membrane structure predominating in excitation-contraction coupling (5,6,14,39,47,50,56,62), it is fascinating to speculate that the role of the sarcolemmal KCNQ1 channels is distinct from the T-tubular KCNQ1 channels. Whereas the most obvious function of T-tubular KCNQ1 channels is to counteract and overrule the depolarizing action of the Ca 2ϩ currents (DHPR) during the repolarization of the cardiac action potential, the sarcolemmal KCNQ1 channels could play another role.…”
Section: Subcellar Localization Of Erg1 and Kcnq1mentioning
confidence: 99%
“…The sources of Ca 2+ that enters the cell across the sarcolemma are considered to be the extracellular space and Ca 2*-binding sites within the sarcolemmal membranes [24][25][26]. Langer et al [24][25][26] reported that membrane bound Ca 2+ in cardiac cell is a superficial store of Ca 2 § which becomes available for entry upon excitation of the myocardium.…”
Section: A Tp-independent Ca2*-bindingmentioning
confidence: 99%